An investigation of the possibility of non-Laurentide ice stream contributions to Heinrich event 3. (May 2021) - Velay-Vitow, Jesse; Peltier, W. Richard; Stuhne, Gordan R.
Abstract: The ocean floor sedimentological signature of Heinrich event 3 (H3) is markedly different from that of other Heinrich events that are known to have originated in Hudson Strait. It has therefore been suggested that the H3 contribution to iceberg flux may have been delivered by ice streams located in the eastern sector of the North Atlantic, from the Fennoscandian or British Isles ice sheets. To investigate this possibility and whether the instability involved may have been tidally induced, as seems to have been the case for H1, we consider several eastern Atlantic sector possibilities: a hypothetical Barents Sea ice stream, the Norwegian ice stream, and the Irish Sea ice stream. We find that the extremely high amplitude of the M2 tidal constituent in the western North Atlantic that appears to have forced H1 did not exist in the northeastern Atlantic. This suggests that, with one possible exception, if destabilized ice streams in this region did contribute to H3, tidal forcing was most probably not the cause. The single exception to this general conclusion may be the Irish Sea ice stream, and we comment on the probability of a contribution to H3 from this source.